Fraud survival in nonprofit organizations: Empirical evidence. Issue 1 (16th April 2018) - Archambeault, Deborah S.; Webber, Sarah
Abstract : This study examines the survival of nonprofit organizations after the discovery of a fraud. Literature on nonprofit fraud claims that fraud has a destructive impact on nonprofit organizations. This study is the first to provide empirical evidence of the impact of fraud on a nonprofit organization's survival, and to analyze the significance of underlying organizational and fraud factors. An analysis of 115 nonprofit organizations experiencing a fraud shows that over one fourth of these organizations did not survive at least 3 years beyond the publication of the fraud, a rate considerably higher than the typical nonprofit failure rate. This article investigates the characteristics of surviving organizations and finds that older and larger organizations are more likely to survive, indicating the liabilities of newness and smallness hold in fraud survival situations. In cases where an executive‐level perpetrator committed the fraud, or where the organization victimized the public, the organization was less likely to survive. These findings suggest nonprofit organizations, particularly those that are new or small, could benefit by implementing governance policies and procedures that are consistent with those employed by more established organizations.